Physical activity and risk of cardiovascular events and all-cause mortality among kidney transplant recipients. Issue 8 (21st May 2020) - Kang, Augustine W; Bostom, Andrew G; Kim, Hongseok; Eaton, Charles B; Gohh, Reginald; Kusek, John W; Pfeffer, Marc A; Risica, Patricia M; Garber, Carol E
Abstract: Background: Insufficient physical activity (PA) may increase the risk of all-cause mortality and cardiovascular disease (CVD) morbidity and mortality among kidney transplant recipients (KTRs), but limited research is available. We examine the relationship between PA and the development of CVD events, CVD death and all-cause mortality among KTRs. Methods: A total of 3050 KTRs enrolled in an international homocysteine-lowering randomized controlled trial were examined (38% female; mean age 51.8 ± 9.4 years; 75% white; 20% with prevalent CVD). PA was measured at baseline using a modified Yale Physical Activity Survey, divided into tertiles (T1, T2 and T3) from lowest to highest PA. Kaplan–Meier survival curves were used to graph the risk of events; Cox proportional hazards regression models examined the association of baseline PA levels with CVD events (e.g. stroke, myocardial infarction), CVD mortality and all-cause mortality over time. Results: Participants were followed up to 2500 days (mean 3.7 ± 1.6 years). The cohort experienced 426 CVD events and 357 deaths. Fully adjusted models revealed that, compared to the lowest tertile of PA, the highest tertile experienced a significantly lower risk of CVD events {hazard ratio [HR] 0.76 [95% confidence interval (CI) 0.59–0.98]}, CVD mortality [HR 0.58 (95% CI 0.35–0.96)] and all-cause mortality [HR 0.76 (95% CI 0.59–0.98)]. Results were similar in unadjusted models. Conclusions: PA was associated with a reduced risk of CVD events and all-cause mortality among KTRs. These observed associations in a large, international sample, even when controlling for traditional CVD risk factors, indicate the potential importance of PA in reducing CVD and death among KTRs. Graphical Abstract: